Factors related to retinal haemorrhage in infants born at high risk. Issue 6 (3rd July 2017) - Pu, Qinglan; Li, Ping; Jiang, Huiqin; Wang, Hong; Zhou, Qiaoyun; Liu, Jia; Zhong, Wenhua; Huang, Huafei
Abstract: Purpose: This study aims to determine risk factors for retinal haemorrhage (RH) in high‐risk infants. Methods: A total of 3123 cases with high‐risk pregnancy and/or neonatal asphyxia 72 hr after delivery were enrolled into this study. Fundus examinations were performed on newborns utilizing a wide‐angle imaging system (RetCam III). Retinal haemorrhage (RH) was classified into three grades. Maternal, obstetric and neonatal parameters from high‐risk infants with RH were compared with parameters from infants without RH. Results: Retinal haemorrhage (RH) was found in 550 (18%) of 3123 high‐risk infants. Retinal haemorrhage (RH) was classified as grade I (39%), grade II (24%) and grade III (37%). Monocular RH occurred in 37% of cases, while the remaining cases were binocular. Moreover, six cases had vitreous haemorrhage. The following parameters correlated (p < 0.05) with RH in this study: delivery mode ( χ 2 = 469), gestational age ( χ 2 = 35), birth weight ( χ 2 = 18), asphyxia ( χ 2 = 73), scalp hematoma ( χ 2 = 55), maternal age ( χ 2 = 8.9), precipitate labour ( χ 2 = 120) and delivery times ( χ 2 = 6.1). Logistic regression analysis indicated that delivery mode and asphyxia were risk factors for RH in high‐risk infants, with odds ratios of 0.827 and 2.5, respectively. Gender, intracranial haemorrhage and foetal distress were not correlated with RH in high‐risk infants. Conclusion: The incidence of RH in high‐risk infants was 18%, and delivery mode, and neonatal asphyxia were major risk factors for RH in high‐risk infants.